2018
DOI: 10.3917/rfas.181.0125
|View full text |Cite
|
Sign up to set email alerts
|

Le Régime d’assistance médicale (RAMed) au Maroc : les mécomptes du volontarisme et de l’opportunisme

Abstract: L'article porte sur le Régime d'assistance médical (RAMed) mis en place au Maroc à partir de 2011. Ce régime accorde la gratuité des soins dans le système hospitalier. Proposant un avantage indéniable à une importante population de pauvres et de vulnérables, il présente, toutefois, d'importantes faiblesses, notamment en ce qui concerne la continuation des paiements des ménages, les files d'attentes et les transports des patients. De plus, le mécanisme de financement du dispositif n'a jamais été mis en oeuvre, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Following the examples of Algeria, 4 Tunisia, 5 or Morocco, 6 Mali is one of the rare West African countries to have a public policy designed to provide free access to health services for indigents. 7 For operational purposes, Malian officials decided that indigents would represent the poorest 5% of the general population in Mali.…”
Section: Discussionmentioning
confidence: 99%
“…Following the examples of Algeria, 4 Tunisia, 5 or Morocco, 6 Mali is one of the rare West African countries to have a public policy designed to provide free access to health services for indigents. 7 For operational purposes, Malian officials decided that indigents would represent the poorest 5% of the general population in Mali.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, RAMED mainly works by relying on the normal state subsidies that hospitals receive. 20 The generalisation of RAMED in 2012 led to an explosion in overall healthcare demand and put considerable pressure on public hospitals, unable to absorb it. According to RAMED operating procedures, 21 the patientto-be shall first go to the nearest public health centre, the name of which is written on his/her beneficiary card.…”
Section: Realising the Right To Health In Morocco: Access And Barriersmentioning
confidence: 99%
“…Whilst the compulsory health insurance scheme (Assurance Maladie Obligatoire) financing presents fewer challenges [24], the scheme for the poor (RAMED) is still struggling to achieve its objectives. The RAMED was generalised since 2012 and always strives to ensure equity of access to health services, reducing financial hardship and providing sustainable financing for the scheme [25,26]. Another study using longitudinal data from 2013 to 2015 showed an increase in household expenditure associated with the generalisation of RAMED [27].…”
Section: Introductionmentioning
confidence: 99%